Terminal RFLP analysis to determine the oral microbiota with hyposalivation - Hayashi, Y; Saito, T; Ohshima, T; Nakagawa, Y; Arita, T; Yashima, A; Makino, T; Konnai, R; Gomi, K; Arai, T; Maeda, N (Archives of microbiology, 2014)
Previous studies of oral microbiota by culture-dependent or targeted DNA approaches demonstrated that hyposalivation, a reduction in salivary secretions, might increase the amount of certain oral pathogens. However, the relationship between hyposalivation and the balance of oral microbiota, especially uncultivable bacteria, remains still unclear. The aim of this study was to elucidate the relationship between hyposalivation and oral microbiota by analyzing terminal restriction fragment length polymorphism (T-RFLP) of 16S rDNA. The 61 subjects were divided into two groups, hyposalivation group and normo-salivation group. The microbiota of tongue-coating samples was analyzed by T-RFLP. The amount of saliva, the number of Candida albicans, and also the dental status including plaque index, gingival index, bleeding on probing, probing pocket depth and decayed, missing, and filled teeth (DMFT) were assessed. Regarding the dental status, none of the evaluated factors were significantly different between the groups except the number of DMFT. According to the T-RFLP profiles, the patterns of microbiota in the tongue coating were classified into two groups, Clusters I and II. Cluster I is made up 76 % of subjects with hyposalivation, while Cluster II is made up 61 % of subjects with normo-salivation (p < 0.001). Compared with the microbiota found in Cluster II, that in Cluster I had higher proportions of T-RFs corresponding to genera Veillonella, Dialister, Prevotella, Fusobacterium, and Streptococcus. T-RFLP analysis showed a significant role of salivary volume in determining the composition of the microbial community, regardless of the cultivability of the bacteria.